IGF-1 levels in the general population, heart failure patients, and individuals with acromegaly: differences and projections from meta-analyses—a dual perspective - Hu, Yan; Jiang, Yinling; Duan, Lixia; Yang, Songwei; Tuniyazi, Subinur; Zou, Jianghua; Ma, Rui; Muhemaitibieke, Gulina; Amuti, Xiayidanguli; Guo, Yanying (Frontiers in Cardiovascular Medicine, 2024)
BackgroundThe complex relationship between insulin-like growth factor 1 (IGF-1) levels and heart failure (HF) is not fully understood, particularly across different populations and conditions. This meta-analysis aims to elucidate the dual perspectives of IGF-1 levels in the general population, HF patients, and individuals with treatment-naïve acromegaly, highlighting IGF-1 as a biomarker and potential therapeutic target in HF management.MethodsStudies were searched across multiple electronic databases up to January 2024 and independently identified by reviewers. The outcomes were analyzed using RevMan 5.4 and STATA 15.ResultsA total of 25 articles were ultimately included in the analysis. Six studies compared IGF-1 levels between HF patients and non-HF controls, revealing significantly lower IGF-1 levels in HF patients (mean difference −20.93; 95% CI −37.88 to −3.97; p = 0.02). This reduction was consistent across various HF subtypes and severities. In addition, individuals with intermediate IGF-1 levels had a lower risk of developing HF [risk ratio (RR) 0.78; 95% CI 0.74–0.83; p < 0.01] and HF-related mortality (RR 0.98; 95% CI 0.97, 0.99; p < 0.01) compared to those with low IGF-1 levels, suggesting a protective role for maintaining adequate IGF-1 levels. Conversely, treatment-naïve acromegaly patients, characterized by excessively high IGF-1 levels, showed a significantly higher incidence of both diastolic HF [odds ratio (OR) 9.08; 95% CI 6.20–13.29; p < 0.01] and systolic HF (OR 13.1; 95% CI 6.64–25.84; p < 0.01), implicating supraphysiological IGF-1 levels in adverse cardiac outcomes.ConclusionsOur meta-analysis highlights the complex interplay between IGF-1 levels and HF. We found that reduced IGF-1 levels are commonly observed in HF patients and are associated with an increased risk of HF and higher HF-related mortality. Conversely, excessively high levels, as observed in acromegaly, are linked to a higher incidence of HF. Based on these results, it is recommended that cardiac function be closely monitored in patients with reduced IGF-1 levels and in those with acromegaly. These findings suggest that IGF-1 could hold potential prognostic value for risk stratification in HF.